On the information content in linear horizontal delay gradients estimated from space geodesy observations - Elgered, Gunnar; Forkman, Peter; Haas, Rüdiger; Ning, Tong (Chalmers University of Technology, 2019)
The data are produced for a scientific article, https://doi.org/10.5194/amt-2018-318, with the following abstract:

We assess the quality of estimated linear horizontal gradients in the atmospheric propagation delay above ground-based stations receiving signals from the Global Positioning System (GPS). Gradients are estimated from 11 years of observations from five stations in Sweden. Comparing these gradients with the corresponding ones from the European Centre for Medium-Range Weather Forecasts (ECMWF) analyses show that GPS gradients confirm known seasonal effects both in the hydrostatic and the wet components. The two GPS stations equipped with microwave absorbing material below the antenna in general show higher correlation coefficients with the ECMWF gradients compared to the other three stations. We also estimated gradients using GPS data from two collocated antenna installations at the Onsala Space Observatory. Correlation coefficients for the east and the north wet gradients from GPS can for specific months reach up to 0.8 when compared to simultaneously estimated wet gradients from microwave radiometry. The best agreement is obtained when an elevation cutoff angle of 3° is applied in the GPS data processing, in spite of the fact that the radiometer does not observe below 20°. Based on the four years of results we note a strong seasonal dependence in the correlation coefficients, from 0.3 during months with smaller gradients to 0.8 during months with larger gradients, typically during the warmer, and more humid, part of the year. Finally, a case study using a 15-day long continuous Very Long Baseline Interferometry (VLBI) campaign was carried out.
The comparison of the gradients estimated from VLBI and GPS data indicates that a homogeneous and frequent sampling of the sky is a critical parameter.

Datamängden består av atmosfärsmätningar med hjälp av signaler från globala satellitbaserade navigationssystem. Data är insamlade vid fem platser i Sverige, från 2006 till 2016. Speciellt fokus är på Onsala rymdobservatorium där atmosfärsskattningar från två GNSS-stationer jämförs med motsvarnade skattningar gjorda med data från mikrovågsradiometri och långbasinterferomtri (VLBI = Very Long Baseline Interferomtry) under perioden 2013–2016.
Horisontella atmosfärsgradienter skattade med hjälp av rymdgeodetiska tekniker
Keywords: Atmospheric conditions; Atmosfäriska förhållanden; Meteorological geographical features; Geografiska meteorologiska förhållanden; atmospheric horizontal gradients; atmosfäriska horisontella gradienter; microwave radiometry; mikrovågsradiometri; atmospheric remote sensing; atmosfärisk fjärranalys; GNSS; GNSS; Natural Sciences; Naturvetenskap; Earth and Related Environmental Sciences; Geovetenskap och relaterad miljövetenskap; Geoscientific Information; Geovetenskap